Vocabulary building in relation to language teaching - Yazon, Francisca (Olivares) 1929- ([Quezon City s.n.], 1964)
This study explores the possibility of teaching vocabulary building for better language teaching at the high school level. Sample exercises and lessons are presented to show how this may be accomplished. Aside from being taught in correlation with sound, structure, reading, writing and literature, vocabulary may also be taught as vocabulary.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Language and languages -- Study and teaching